Estudo estereofotogramétrico da cinemática da cabeça de indivíduos com estresse visual - Cláudia de Almeida Ferreira Diniz (2017)
The present study investigated the motor behavior of moving the head in space, in situations where it should remain still, observed in subjects with Visual Stress (VS). Such investigation is relevant because these movements change the orbits position in space, which may contribute to the subjects symptoms. For the investigation a stereophotogrametric system was developed specifically to register the head motion. It differs from commercially available systems since: 1) it is specific to quantify such motion at the most relevant anatomic point when the analysis is related to the visual system, besides not causing interference on the ocular motion; 2) it is of simple operation and assemble, intended for clinical use; 3) it is of low cost, since two camcorders and a free software were used. For the system, an algorithm was developed to calculate the head motion at six degrees of freedom, translated to the middle point between the eyes. For data analysis, clinically relevant variables for VS were selected together with two methodologies originally applied to this application: 1) the use of human vibration parameters to describe and analyse the head motor behaviour of subjects with VS; and 2) the use of the Modal Assurance Criterion (MAC) to correlate head motion vectors in the tested situations. The system was applied in a clinical experiment with a group of subjects with VS, in order to characterize their kinematic head motion and to verify the effects of the body posture, the use of vision and the visual tasks performance on their kinematic control. The results show that the volunteers with VS used in the experiment kept their head in continuous movement, although their mean motion velocity was kept close to zero over time. Their kinematic control was characterized by high variance and acceleration values, reaching levels that may be considered dangerous for health. The motion vector correlation revealed the kinematic characteristics of a motor system having high dimentionality, high inter subject variability and influenced by the use of vision, the body posture and the visual task performed.